PENGARUH PENGETAHUAN PERPAJAKAN, KETEGASAN SANKSI PAJAK, DAN TAX AMNESTY TERHADAP KEPATUHAN WAJIB PAJAK - Nurulita Rahayu (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aims to examine the influence of tax knowledge, firmness of tax sanctions, and tax amnesty against about obedience to taxpayer. This study focus on taxpayers every people who were in district of Bantul to know: (1) Influence of knowledge about obedience taxpayer, (2) Influence of assertiveness tax sanctions to taxpayer, and (3) Influence of tax amnesty against of docility taxpayers.Used data is the primary data from the spread of the questionnaire to 127 respondents and data that can be processed as much as 85 questionnaires. Method of sample collectionÂ is use convenience sampling. Technique used data analysis is the technique of regressing linear doubled.Regression test results showed that (1) knowledge of tax that influence of positive and significant about obedience taxpayers, (2) assertiveness tax sanctions that influence of positive and significant about obedience taxpayers, and (3) tax amnesty influential positive and significant about obedience taxpayers. The magnitude of the influence variable independent seen from the value of the coefficient determination (R2) of 0,509, which means that the knowledge of tax, assertiveness sanctions taxes, and tax amnesty give the influence of positive towards of docility taxpayers of 50,9.Keywords: the knowledge of taxes, assertiveness taxes sanctions, tax amnesty and assertiveness taxpayers.